Neotypification of Pandanus odorifer, the correct name for P. odoratissimus (Pandanaceae). Issue 1 (12th November 2020) - Callmander, Martin W.; Gallaher, Timothy J.; McNeill, John; Beentje, Henk; Nadaf, Altafhusain B.; Middleton, David J.; Buerki, Sven
Abstract: Pandanus odorifer (Pandanaceae) is an economically important species distributed on coasts from India and Sri Lanka to South China through tropical Asian countries. Pandanus odoratissimus has been widely used as the accepted name for the species, but P. odoratissimus is in reality a superfluous and illegitimate name. No original material of P. odorifer has been traced, and a neotype is designated here for that name.